Lesson study: A cross-cultural analysis between the Philippines and Viet Nam - Romiro G Bautista; Wilfredo B Baniqued; Thi Thuy Diem Huynh; Thinh Mai Phuc (CTU Journal of Innovation and Sustainable Development)
Lesson study is a type of teacher-driven study in Japan in which teachers work together to enhance a specific aspect of their students’ learning. It is a cycle of inquiry that encourages instructors to try, observe, and improve. This paper compares respondents’ understanding of lesson study’s educational potential in various dimensions, analyzing relationships and testing a theoretical model to explain factors influencing its employment in specific educational settings. The study utilized quantitative research and comparative analysis to compare lesson study methods in Quirino, Philippines, and Can Tho, Viet Nam, examining connections between variables. The results show that respondents in their various school and classroom cultures have a generally positive attitude about the setting up and carrying out of the lesson study. The apparent disparity in reactions between Quirino, Philippines, and Can Tho, Viet Nam highlights the importance of local educational traditions and regulations on lesson study adoption. Because of the dynamic interaction between nations, age groups, and views of lesson study, educational institutions may build focused interventions that address specific challenges, utilize generational strengths, and foster a collaborative environment favorable to improve teaching quality.